2016
DOI: 10.3389/fpls.2016.00353
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of the GRAS Gene Family in Grapevine Indicates a Role of GRAS Proteins in the Control of Development and Stress Responses

Abstract: GRAS transcription factors are involved in many processes of plant growth and development (e.g., axillary shoot meristem formation, root radial patterning, nodule morphogenesis, arbuscular development) as well as in plant disease resistance and abiotic stress responses. However, little information is available concerning this gene family in grapevine (Vitis vinifera L.), an economically important woody crop. We performed a model curation of GRAS genes identified in the latest genome annotation leading to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
102
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 89 publications
(164 reference statements)
13
102
0
1
Order By: Relevance
“…This number is lower than that in Malus domestica (127) [28], Populus (106) [20], and maize (86) [27] but higher than that in Arabidopsis (34) [20], rice (60) [20], Chinese cabbage (48) [19], Prunus mume (46) [21], tobacco (53) [22], castor (48) [23], grapevine (52) [24], Medicago truncatula (68) [25,26], pepper (50) [29], and tea plant (52) [30]. This variation in GRAS gene numbers might be related to gene duplication events or genome size [24]. Four groups of tandem duplicated MeGRAS genes and 34 pairs of segmental duplicated MeGRAS genes were detected in this study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This number is lower than that in Malus domestica (127) [28], Populus (106) [20], and maize (86) [27] but higher than that in Arabidopsis (34) [20], rice (60) [20], Chinese cabbage (48) [19], Prunus mume (46) [21], tobacco (53) [22], castor (48) [23], grapevine (52) [24], Medicago truncatula (68) [25,26], pepper (50) [29], and tea plant (52) [30]. This variation in GRAS gene numbers might be related to gene duplication events or genome size [24]. Four groups of tandem duplicated MeGRAS genes and 34 pairs of segmental duplicated MeGRAS genes were detected in this study.…”
Section: Discussionmentioning
confidence: 89%
“…GRAS genes have recently been studied in various plant species, i.e., Arabidopsis [18], rice [18], Chinese cabbage [19], Populus [20], Prunus mume [21], tobacco [22], castor bean [23], grapevine [24], Medicago truncatula [25,26], maize [27], Malus domestica [28], pepper [29], and tea plant [30]. According to previous studies in Arabidopsis and rice [18], the GRAS family members can be classified into eight subfamilies: the DELLA, HAM, LAS, PAT1, SCR, SHR, SCL3, and LISCL subfamilies.…”
Section: Introductionmentioning
confidence: 99%
“…These nine members may have similar functions. It has been reported that the HAM and LS families In order to help with PgGRAS classification and decipher the evolution history of the PgGRAS gene family in ginseng, we built two evolutionary trees and applied 67 genes (Ginseng and Arabidopsis) (Figure 2a; Tables S2 and S3) and 172 genes (Ginseng, Arabidopsis, Tomato and Rice) (Figure 2b; Tables S2 and S3), respectively [46,47]. As shown in Figure 2, we identified a total of 15 sub-families of the GRAS genes.…”
Section: Conserved Motif Analysis and Systematic Analysis Of Pggras Gmentioning
confidence: 99%
“…The publication of the grapevine ( Vitis vinifera ) genome sequence in 2007 facilitated the functional analysis of a number of gene families characterised in other species to determine whether these could be used to improve the performance of this economically important fruit crop33343536373839. The E3 ubiquitin ligase family has not been investigated thus far, and only one grapevine RING-type E3 ubiquitin ligase has been functionally characterised: the EIRP1 protein from the wild species V. pseudoreticulata .…”
mentioning
confidence: 99%